SURAT PAKSA SEBAGAI INSTRUMEN PENAGIHAN PAJAK DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK PADA KPP PRATAMA PEKANBARU TAMPAN - Herman, Ayuthia Ramadhani; Antoni. R, Stevanus (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study was to determine the extent of the impact of tax collection using warrants on taxpayer compliance. Data analysis used in this study included statistical analysis, validity and reliability tests, normality tests, simple regression analysis, simple correlation analysis, t-tests, and R2 tests. The results of the simple correlation analysis showed that the correlation between tax collection and warrants was 0.716, exceeding 0.05. This indicates that tax collection using warrants has an impact on taxpayer compliance.The results of the t-test showed that the calculated t for the variable